Precision of Single-Skill Math CBM Time-Series Data: The Effect of Probe Stratification and Set Size. (27th December 2019) - Solomon, Benjamin G.; Payne, Lexy L.; Campana, Kayla V.; Marr, Erin A.; Battista, Carmela; Silva, Alex; Dawes, Jillian M.
Comparatively little research exists on single-skill math (SSM) curriculum-based measurements (CBMs) for the purpose of monitoring growth, as may be done in practice or when monitoring intervention effectiveness within group or single-case research. Therefore, we examined a common variant of SSM-CBM: 1 digit × 1 digit multiplication. Reflecting how such measures are often used in contemporary research and practice, we examined the comparative reliability of three representative SSM-CBM set sizes of 8, 16, and 32 unique problems. In a separate study, we investigated the possible benefit of stratifying problems within operation and probe relative to random assignment. Findings suggest that SSM-CBM slope reliability benefits from explicit stratification and that set size is a relevant consideration. Implications for the selection and interpretation of SSM-CBMs when engaging in practice and research are discussed.